MEMBENTUK SIKAP TAWADHU’ SISWA MELALUI KETELADANAN GURU PENDIDIKAN AGAMA ISLAM - Almuniroh, Siti; Ilahiyah, Iva Inayatul (EL-Islam, 2023)
Abstract: The teacher as an educator is responsible for shaping the personality of students. He is a role model in every activity, both in educational institutions and in society in everyday life. Islamic Religious Education (PAI) teachers not only teach religious material but are expected to be able to set an example, especially humility. In this study, it will examine efforts to form students' humble attitudes through the example of Islamic Religious Education (PAI) teachers. The qualitative method is a way of describing the role of the Islamic Religious Education teacher as uswah (example) and several factors that support or hinder the teacher as uswah (exemplar) in the attitude of tawadhu' in their students. Because PAI teachers have an important role in their daily lives, including as community leaders, ustadz, teachers, religious leaders, and clerics, they are not enough to teach Islamic religious knowledge to educational institutions, but practice and spread Islamic teachings in people's lives.